Simultaneous recordings of velocity and video during swimming - Craig, A. B.; Termin, B.; Pendergast, D. R. (Biomechanics and Medicine in Swimming X, 2006)
A method is described for the recording a swimmer's velocity and synchronizing these records with the underwater video. Examples of these records during pushing off from the side of the pool, breaststroke, butterflystroke, backstroke, and crawlstroke are presented. These records demonstrate to swimmers and coach the biomechanics of swimming, and they are useful for immediate feedback.